Level of protein and energy on the in vitro fermentation of diets for lambs - De la Rosa- Zariñana, Asael Edem; Miranda-Romero, Luis Alberto; Martínez-Hernández, Pedro Arturo; Vargas-Villamil, Luis Manuel; Elmasry, Amr (Ecosistemas y Recursos Agropecuarios, 2023)
The ruminal utilization efficiency of the feed, among other reasons, depends on the level of energy and protein it contains. To determine the effect of the energy and protein level of the feed on digestibility (IVMD72h), volume (Vm), rate (S) and Lag phase (L) of gas production; the fast (FFR), medium (MFF) and slow (SFF) fermentation fractions; methane production, the global warming potential indicator (GWPI) and environmental impact index (EII), five diets were formulated according to the level of metabolizable energy (ME, Mcal kg−1 DM) and crude protein (PC , %); BB; 2.6 and 13.8, MM; 2.8 and 16, AA; 3.0 and 17.2, AB; 2.8 and 14.5, BA; 2.6 and 17.2 on EM and PC. The S was higher (p < 0.05) in the AA and AB diets, the Vm was lower (p < 0.05) for the BA diet. The AA diet had the highest (p < 0.05) FFR and FFM. The BA and BB diets had the highest (p < 0.05) FFL, but the lowest IVMD72h (p < 0.05). Regarding the environmental impact, the BB diet produced the highest proportion (p < 0.05) of CH4, GWPI and EII. It is concluded that diets with a higher content of non-structural carbohydrates have better fermentative kinetics and digestibilities, they also generate lower proportions of CH4, IPCG and EII, the latter can be used as indicators of environmental impact since they consider the CO2 and CH4 produced by the consortia. rumen microbials.